Application of bioactive metal ions in the treatment of bone defects. Issue 45 (15th November 2022) - Li, Shaorong; Cui, Yutao; Liu, He; Tian, Yuhang; Wang, Gan; Fan, Yi; Wang, Jingwei; Wu, Dankai; Wang, Yanbing
Abstract : In recent years, the research of metal ions has become more extensive in bone tissue engineering. We review the mechanism and application of metal ions in the treatment of different pathological types of bone defects in bone tissue engineering. Abstract : The treatment of bone defects is an important problem in clinical practice. The rapid development of bone tissue engineering (BTE) may provide a new method for bone defect treatment. Metal ions have been widely studied in BTE and demonstrated a significant effect in promoting bone tissue growth. Different metal ions can be used to treat bone defects according to specific conditions, including promoting osteogenic activity, inhibiting osteoclast activity, promoting vascular growth, and exerting certain antibacterial effects. Multiple studies have confirmed that metal ions-modified composite scaffolds can effectively promote bone defect healing. By studying current extensive research on metal ions in the treatment of bone defects, this paper reviews the mechanism of metal ions in promoting bone tissue growth, analyzes the loading mode of metal ions, and lists some specific applications of metal ions in different types of bone defects. Finally, this paper summarizes the advantages and disadvantages of metal ions and analyzes the future research trend of metal ions in BTE. This article can provide some new strategies and methods for future research and applications of metal ions in the treatment of bone defects.